STUDY THERMAL OF COMPRESSOR POWER REDUCTION ON USING SOLID DRY PAD PRE-AIR COOLING SYSTEM - Surya, I Gede Teddy Prananda; Wijaksana, Hendra (Jurusan Teknik Mesin Fakultas Sains dan Teknik Universitas Bangka Belitung, 2023)
AbstractThe uses of compressor based air conditioning system has rapidly increased the consumption of fossil fuel energy resources and the degradation of environment quality. Massive study has been done worldwide to reduce energy consumption for compressor based air conditioning (AC) system. This study is subjected to investigate the use of solid dry pad as pre-air cooling for AC system. In this study, solid dry pad would be placed in the evaporator and condenser inlet air side. This placement was objected to give a pre-cooling effect for evaporator and condenser inlet air, so then the compressor could be operated with a lower power consumption. The experiment would be carried out within three level air mass flowrate of 0.293 kg/s; 0.319 kg/s; and 0.359 kg/s, for air velocity of 2.2; 2.4; and 2.7 m/s respectively, the cooling cabin is set into 30oC using a heater as a cooling load. As a results, it could be revealed that at the highest air mass flowrate of 0.359 kg/s, it could achieved the lowest compressor power consumption of 0.44 kW, within a higher cooling capacity of 2.625 kW, a higher condenser heat rejection of 3.622 kW and also higher COP of 5.9. Referring to those results, it can be concluded that when employing solid dry pad pre-air cooling for evaporator and condenser AC system, it could reduced compressor power consumption by 12.2%; 21.9% and 20% for air velocity of 2.2; 2.4; and 2.7 m/s respectively.Keywords : solid dry pad, pre-air cooling, compressor power reduction.